Co-harboring of Novel blaKPC–2 Plasmid and Integrative and Conjugative Element Carrying Tn6203 in Multidrug-Resistant Pseudomonas aeruginosa - Cai, Heng; Zhu, Yiwei; Hu, Dandan; Li, Yue; Leptihn, Sebastian; Loh, Belinda; Hua, Xiaoting; Yu, Yunsong (Frontiers in Microbiology, 2021)
Many strains of the opportunistic pathogen Pseudomonas aeruginosa have acquired resistance to multiple antibiotics. Carbapenem-resistant P. aeruginosa poses a global healthcare problem due to limited therapeutic options for the treatment of infections. Plasmids and integrative and conjugative elements (ICEs) are the major vectors of antibiotic-resistance gene transfer. In our study, four carbapenem-resistant strains of P. aeruginosa were isolated from the same patient in a tertiary referral hospital in China, one of these was resistant to gentamicin and tobramycin. In this strain P33, we observed a non-transferable plasmid, pP33-2, carrying a novel blaKPC−2 gene segment (ISKpn27-blaKPC−2-ISKpn6-korC-ORF-klcA-IS26), which we concluded to have been formed by IS26-mediated gene cluster translocation. In addition, by comparing the chromosomes of the P. aeruginosa strains that belong to the same sequence type, we identified an ICE, ICEP33, adjacent to a prophage. The attL site of ICEP33 is identical to the terminal part of the attR site of the prophage. The ICEP33 element contains the transposon Tn6203, which encodes antibiotic and metal resistance genes. The insertion of ICEP33 in the chromosome mediates resistance to multiple antibiotics. Our study contributes to the understanding of the acquisition of antibiotic resistance in P. aeruginosa facilitated by mobile genetic elements.